Pengaruh Kepemimpinan dan Supervisi Akademik terhadap metode Pembelajaran Guru di SMA Negeri Se-Kecamatan Sungai Keruh Kabupaten Musi Banyuasin - Andy Yulianto; Tri Widayatsih; Sri Wahyu Indrawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of leadership and academic supervision on teacher learning methods in Public Senior High Schools in Sungai Keruh District, Musi Banyuasin Regency. The research method used is a quantitative method with a survey approach, involving the entire population as well as a sample of 76 Public Senior High School teachers in Sungai Keruh District. Data collection techniques were carried out through questionnaires, observation, and documentation, while data analysis used prerequisite analysis tests, simple linear regression, multiple linear regression, t-test, and F-test. The results showed that the principal's leadership had a significant effect on teacher learning methods with a t-value of 2.547 greater than t-table 1.290 and a significance of 0.013 <0.05. Academic supervision also had a significant effect on teacher learning methods with a t-value of 6.472 greater than t-table 1.290 and a significance of 0.000 <0.05. Simultaneously, leadership and academic supervision have a significant effect on teacher learning methods as indicated by the calculated F value of 20.658 which is greater than Ftable 3.117 with a significance of 0.000 < 0.05. The conclusion is that the principal's leadership and academic supervision, both partially and simultaneously, have a significant effect on teacher learning methods in State Senior High Schools in Sungai Keruh District, Musi Banyuasin Regency, so that effective leadership and implementation of academic supervision are needed to improve the quality of learning. Keywords: Leadership, Academic Supervision, High School Teachers, Principals